Multimorbidity daily life activities and socio-economic classification in the Central Portugal primary health care setting: an observational study - Santiago, Luiz Miguel de Mendonça Soares (2020)
Background. Multimorbidity (MM) is associated with decreased quality of life, mainly due to decreased functional capacity and increased use of health care. Objectives. Evaluate the prevalence of MM in older people of Central Portugal and understand the impact of MM on daily life activities (DLA) and how socioeconomic level influenced prevalence of MM. Material and methods. Observational study of data on age, sex, number of ICPC2 codes and Barthel (Bt) and Graffar (Gr) Indexes in clinical records of all aged between 65 to 99 years enrolled in the Health Centers of the Central Region of Portugal. The Bt was used to assess the dependence on DLA and the Gr the socioeconomic level. Results. Population of 190025, mean age of 80.16± 8.03 years. MM prevalence of 80% out of which, 52.9% were female and the majority was aged between 76-85 years (39.1%). Average number of health problems of 8.7 problems for males and 9.5 for females. The Bt and Gr Indexes filling for the studied sample were of, Barthel 7.4% and Graffar 4,9%. Older people without MM have higher dependency rates than those with MM (total dependence 7.4% vs 6.2% and severe dependence 20.1% vs 9.6%). MM in older people are mainly in the middle (55.3% vs 27.5%) and low (31.8% vs 19.6%) Graffar class, while the older people without MM are mainly at middle to upper (35.3%) and upper (17.6%) Graffar classes. Conclusions. Multimorbidity is mainly associated with lower social classes. Dependence for DLA appears unrelated to MM. Multimorbidity persons need special attention, based on socio-economic contexts.